Improving market outcomes: A qualitative assessment of the Greek dairy supply chain - KOUTOUZIDOU, G.; RAGKOS, A.; KOUTSOU, S.; THEODORIDIS, A. (Journal of the Hellenic Veterinary Medical Society, 2020)
This study provides a qualitatative assessment of the overall outcomes of the dairy supply chain in Greece. Based on the framework of the Taskforce for Agricultural Markets, a questionnaire survey with in-depth interviews was conducted to farmers, industries and supermarkets in Greece in order to gain knowledge about trading practices, market transparency, risk management, contracts, access to finance and the role of Producer Organizations. The analysis did not reveal significant unfair trading practices and showed positive prospects for the overall supply chain.